Human Adipose-Derived Hydrogel Characterization Based on In Vitro ASC Biocompatibility and Differentiation - Omair A. Mohiuddin; Benjamen T. O'Donnell; J. Nicholas Poche; Rida Iftikhar; Rachel M. Wise; Jessica M. Motherwell; Brett Campbell; Suzana D. Savkovic; Bruce A. Bunnell; Daniel J. Hayes; Jeffrey M. Gimble (Hindawi Limited, 2019)
Hydrogels serve as three-dimensional scaffolds whose composition can be customized to allow attachment and proliferation of several different cell types. Extracellular matrix-derived hydrogels are considered close replicates of the tissue microenvironment. They can serve as scaffolds for in vitro tissue engineering and are a useful tool to study cell-scaffold interaction. The aim of the present study was to analyze the effect of adipose-derived stromal/stem cells (ASCs) and decellularized adipose tissue-derived (DAT) hydrogel interaction on ASC morphology, proliferation, differentiation, and DAT hydrogel microstructure. First, the ASCs were characterized using flow cytometry, adipogenic/osteogenic differentiation, colony-forming unit fibroblast assay and doubling time. The viability and proliferation assays showed that ASCs seeded in DAT hydrogel at different concentrations and cultured for 21 days remained viable and displayed proliferation. ASCs were seeded on DAT hydrogel and cultured in stromal, adipogenic, or osteogenic media for 14 or 28 days. The analysis of adipogenic differentiation demonstrated the upregulation of adipogenic marker genes and accumulation of oil droplets in the cells. Osteogenic differentiation demonstrated the upregulation of osteogenic marker genes and mineral deposition in the DAT hydrogel. The analysis of DAT hydrogel fiber metrics revealed that ASC seeding, and differentiation altered both the diameter and arrangement of fibers in the matrix. Matrix metalloproteinase-2 (MMP-2) activity was assessed to determine the possible mechanism for DAT hydrogel remodeling. MMP-2 activity was observed in all ASC seeded samples, with the osteogenic samples displaying the highest MMP-2 activity. These findings indicate that DAT hydrogel is a cytocompatible scaffold that supports the adipogenic and osteogenic differentiation of ASCs. Furthermore, the attachment of ASCs and differentiation along adipogenic and osteogenic lineages remodels the microstructure of DAT hydrogel.